Effect of resistant starch on the intestinal health of old dogs: fermentation products and histological features of the intestinal mucosa - Peixoto, M. C. [UNESP]; Ribeiro, M. [UNESP]; Maria, A. P.J. [UNESP]; Loureiro, B. A. [UNESP]; di Santo, L. G. [UNESP]; Putarov, T. C. [UNESP]; Yoshitoshi, F. N.; Pereira, G. T. [UNESP]; Sá, L. R.M.; Carciofi, A. C. [UNESP] (My University, 2018)
The effects of resistant starch (RS) intake on nutrient digestibility, microbial fermentation products, faecal IgA, faecal pH, and histological features of the intestinal mucosa of old dogs were evaluated. The same formulation was extruded in two different conditions: one to obtain elevated starch cooking degree with low RS content (0.21%) and the other lower starch cooking with high RS content (1.46%). Eight geriatric Beagles (11.5 ± 0.38 years old) were fed each diet for 61 days in a crossover design. Food intake, nutrient digestibility, fermentation products, faecal pH, and faecal IgA were examined via variance analysis. Histological results of intestinal biopsies were assessed via Wilcoxon test for paired data. The morphometric characteristics of large intestine crypts were evaluated via paired t tests (p <.05). Protein, fat, and energy digestibilities were higher for the low-RS diet (p <.05). Dogs receiving the high-RS diet had lower faecal pH and higher values for propionate, butyrate, total volatile fatty acids, and lactate (p <.05). No differences between diets were found in the histological parameters of the gut mucosa, and only a tendency for deeper crypts in the descending colon was observed for dogs fed the high-RS diet (p =.083). The intake of a corn-based kibble diet manufactured with coarse ground raw material and low starch gelatinization to obtain 1.4% of RS affected microbial fermentation products and faecal pH and tended to increase crypt depth in the descending colon of old dogs.
Keywords: ageing; butyrate; colonocyte; inflammation